Financial Inclusion in India:An Analysis of Pattern and Determinants - Sathiyan, Sanjana; Panda, Prasant Kumar (Indian Journal of Finance, 2016)
The paper analyzed the pattern, progress, and determinants of financial inclusion in India during the post-reform period. Secondary data for 28 Indian states for the years from 2001 and 2011 was used. A multiple regression model was used to examine the determinants. Though India has witnessed an increase in percentage of people accessing banking services, particularly deposits in the post-reform period, a large exclusion of rural people from banking services is still a concern. The regression analysis suggested that the increase in the number of bank accounts availed by households is determined by factors such as the number of bank branches, population dependency per branch, and industry concentration in the state. Socioeconomic factors like per-capita income of the state, literacy rates, and urbanization did not emerge to be significant factors. Branch penetration has played an important role in financial inclusion in India. Effective implementation of the financial literacy programmes and leveraging existing bank branches will help in achieving greater financial inclusion. Incentive-based programs like Jan-Dhan Yojana have an important role to play in this regard.